Family Social Support and Its Impact on Home Care Services in The Elderly - Sulfianti Sulfianti; Rd. Nia Kania Kurniawati; Jean Henry Raule; Bambang Irawan; Anita Lontaan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The presence of home care can help the community in caring for the elderly. However, on the one hand, the elderly often feel left behind, so they then need social support from their families. Then social support will also influence home care services. This research will be carried out to look at how social support can have an impact on home care services in the elderly community. A qualitative approach will be used in this research. The data used in this study comes from various research results and previous studies, which still have relevance to the contents of this research. The results of this study then found that the provision of social support can meet the physical and psychological needs of the elderly at home care. Apart from the elderly, social support from the family can also increase nurses’ performance and reduce stress and burnout. Abstrak: Kehadiran home care dapat membantu masyarakat dalam merawat lansia. Namun di satu sisi, lansia seringkali merasa tertinggal, sehingga mereka kemudian membutuhkan dukungan sosial dari keluarganya. Kemudian dukungan sosial juga akan mempengaruhi pelayanan home care. Penelitian ini akan dilakukan untuk melihat bagaimana dukungan sosial dapat berdampak pada pelayanan home care pada komunitas lansia. Pendekatan kualitatif akan digunakan dalam penelitian ini. Data yang digunakan dalam penelitian ini berasal dari berbagai hasil penelitian dan penelitian sebelumnya yang masih memiliki relevansi dengan isi penelitian ini. Hasil penelitian ini kemudian menemukan bahwa pemberian dukungan sosial dapat memenuhi kebutuhan fisik dan psikologis lansia di panti jompo. Selain lansia, dukungan sosial dari keluarga juga dapat meningkatkan kinerja perawat dan mengurangi stress dan burnout.